Estrategias de marketing digital y el desarrollo del turismo religioso del Santuario Gruta de la Paz, cantón Montufar, Provincia del Carchi - Morillo Suñiga, Cristhel Malenny (2022)
The work carried out is focused on the main Digital Marketing Strategies and the Development of Religious Tourism of the Cave Sanctuary of La Paz, Montufar Canton, Carchi Province, seeks to promote the tourist, cultural and religious development in the Sanctuary. Due to the scarce tourist promotion, and this is reflected in a limited influx of visitors caused mainly by ignorance and little information on digital platforms, written and spoken press, the disinterest of government authorities and due to the Covid-19 pandemic. This sanctuary has a high natural and religious tourist potential attracting the attention of national and foreign tourists who are devotees of the Virgin of Peace. This project aims to improve the accessibility of information on technology platforms often used by all people. The objective of this case study is to examine digital marketing strategies that contribute to the tourist diffusion of the Cave of Peace Sanctuary Canton Montufar, Carchi Province.